Provocation in the System of Communicative Technologies - Иосиф Михайлович Дзялошинский; Роман Владимирович Жолудь (Communications. Media. Design, 2017)
The following article presents a review of the methods and types of provocation as well as the spheres where provocation can be used as a tool of communication. Authors give their opinion about the role and place of provocation in the system of communicative technologies and give different cases of various provocative actions, such as flashmob (including the description of one of the first actions of this kind in Moscow), cityteaser, ambient media, performance, scandal as well as provocative actions, speeches and texts in general.Authors analyse several types of provocators, paying attention to the role of media platforms and their provocative strategy. Two cases from media reality are described. The first case was a scandal with the “Kommersant” newspaper that published the photo of a bulletin with offensive words about Putin. The second case was a scandal with the Russian TV-Channel “Dozhd” (also known as “TV Rain”) that published a poll about the blockade of Leningrad.More cases are about several provocative PR campaigns, such as classics of provocative advertising from “United Colors of Benetton”, Calvin Klein, Dolce & Gabbana, scandalous ads by SuitSupply, Ungaro and AgentProvocateur.Authors give brief examples of provocative questions posed by journalists in the process of Russian political communications, including the examples of questions that were addressed to Vladimir Putin, the president of Russia.